2006
DOI: 10.1038/sj.ki.5000331
|View full text |Cite
|
Sign up to set email alerts
|

Body fat mass and lean mass as predictors of survival in hemodialysis patients

Abstract: A higher body mass index (BMI) is a predictor of better survival in hemodialysis patients, although the relative importance of body fat and lean mass has not been examined in the dialysis population. We performed an observational cohort study in 808 patients with end-stage renal disease on maintenance hemodialysis. At baseline, fat mass was measured by dual-energy X-ray absorptiometry and expressed as fat mass index (FMI; kg/m2). Lean mass index (LMI) was defined as BMI minus FMI. During the mean follow-up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 51 publications
6
113
1
3
Order By: Relevance
“…In the general population, increases in body fat mass causes increases in proinflammatory cytokine levels and decreases in anti-proinflammatory cytokine levels. However, in maintenance hemodialysis patients, it is reported that there is no difference in proinflammatory cytokines based on body fat mass, and the inverse relationship between body fat mass and plasma adiponectin levels are no longer significant (21,24,25). Such changes in adipocytokine profile may be related to survival advantage in maintenance hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, increases in body fat mass causes increases in proinflammatory cytokine levels and decreases in anti-proinflammatory cytokine levels. However, in maintenance hemodialysis patients, it is reported that there is no difference in proinflammatory cytokines based on body fat mass, and the inverse relationship between body fat mass and plasma adiponectin levels are no longer significant (21,24,25). Such changes in adipocytokine profile may be related to survival advantage in maintenance hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Loss of muscle mass is frequently observed in other catabolic diseases as well. 24 It is now widely accepted that muscle atrophy results from the activation of multiple proteolytic systems, including the ubiquitin-proteasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Because decline in serum albumin concentration is more closely associated with Among the subjects with incident MI (n ϭ 632), incident CI (n ϭ 1119), incident CB (n ϭ 473), and any of the three (n ϭ 2098), we examined the factors associated with death after these vascular events by univariate and multivariate logistic regression models including the nine factors in the acute phase proteins rather than dietary protein intake in hemodialysis patients (34), these data may indicate that inflammation was positively associated with incident atherosclerotic CVD in hemodialysis patients. Because BMI correlates positively with both fat mass index and lean mass index in hemodialysis patients (12), a low BMI serves as an integrated index for PEW. In this study, BMI was positively associated with incident MI and inversely with incident CI.…”
Section: Discussionmentioning
confidence: 99%